How can SMEs adopt AI for accounting processes in Singapore despite challenges like cost or technical expertise? - Leong, Pui Yie (2024)
In the 20th-century digital age, the terms "transformation of functions" and "automation of routine maintenance processes" are frequently used to characterize initiatives aimed at boosting productivity and efficiency while, naturally, reducing the cost of recruiting human resources.